Δ3, 2-Hydroxybakuchiol Attenuates Depression in Multiple Rodent Models Possibly by Inhibition of Monoamine Transporters in Brain. (20th June 2018) - Zhao, Gang; Guo, Li-he; Huang, Wei; Hu, Jia-liang
Abstract : Δ 3, 2-Hydroxybakuchiol is isolated from Psoralea corylifolia (L.), which has therapeutic applications in traditional Chinese medicine. Our previous studies have showed that Δ 3, 2-hydroxybakuchiol inhibited the decreased activity of reserpinized mice, suggestive of its antidepressive potential. In this study, we explored the antidepressant profile of Δ 3, 2-hydroxybakuchiol in various rodent models and its possible monoamine-modulating mechanism. Δ 3, 2-Hydroxybakuchiol significantly reduced immobility time of mice in forced swim test and tail suspension test. Δ 3, 2-Hydroxybakuchiol also significantly increased sucrose consumption in chronic unpredictable mild stress (CUMS) rat model. Furthermore, isotope uptake study showed that Δ 3, 2-hydroxybakuchiol inhibited the activity of human dopamine transporter (DAT) and norepinephrine transporter (NET) in transporter-overexpressing pheochromocytoma (PC12) cells with IC50 values similar to the potency of bupropion. Microdialysis showed that Δ 3, 2-hydroxybakuchiol increased dopamine and norepinephrine concentration in rat striatum. In summary, Δ 3, 2-hydroxybakuchiol exerts antidepressant effects on various types of depression models through a possible mechanism of monoamine transporter inhibition.